Hubungan Pengetahuan Ibu Hamil Dengan Kepatuhan Konsumsi Tablet Tambah Darah Di Klinik Fina Sembiring Kecamatan Medan Polonia Kota Medan - Nova Isabella Mariance br. Napitupulu; Ariska Fauzianty; Sonia Novita Sari (Lembaga Pengembangan Kinerja Dosen, 2023)
Anemia during pregnancy is still a global problem throughout the world. Globally, the prevalence of anemia in pregnant women in 2019 was 35.6%. The prevalence of anemia in developing countries is relatively high, such as Southeast Asia at 47.8%, compared to developed countries such as America at 18.9%. The aim is to determine the knowledge of pregnant women regarding compliance with the consumption of blood supplement tablets. This type of research is quantitative with a cross-sectional research design. Population of 43 pregnant women, sample of 43 pregnant women (total sampling). Data analysis with chi square and logistic regression. The results showed a significant relationship between maternal knowledge and compliance with blood supplement tablet consumption with p value = 0.012. Midwives are expected to be able to choose simpler words and language to optimize continuous educational media during counseling, so that pregnant women can more easily understand the counseling provided.